y-7=3(x-4)

Simple and best practice solution for y-7=3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-7=3(x-4) equation:


Simplifying
y + -7 = 3(x + -4)

Reorder the terms:
-7 + y = 3(x + -4)

Reorder the terms:
-7 + y = 3(-4 + x)
-7 + y = (-4 * 3 + x * 3)
-7 + y = (-12 + 3x)

Solving
-7 + y = -12 + 3x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + y = -12 + 7 + 3x

Combine like terms: -7 + 7 = 0
0 + y = -12 + 7 + 3x
y = -12 + 7 + 3x

Combine like terms: -12 + 7 = -5
y = -5 + 3x

Simplifying
y = -5 + 3x

See similar equations:

| 4y=-9x+10 | | 4+6s-1=7s+15-5s | | (2x-1)=x+3 | | 3x+5x-2p+4p= | | 10y+5x=25 | | -11+3x+4=17 | | -7x-8y=12 | | 0=-4 | | 4-4b=8(8+2b) | | x^2-(4p+1)x+(5p^2+2p)=0 | | y=296+7x | | y=7x+296 | | 3(w-2)+7=1-3w | | 4+v=3v-8 | | X=2(0) | | (-5)-(-2)=g+4 | | -60=6x-5y | | 34:4= | | -3(12-6x)=7(8-2x) | | (-35)=c+(-18) | | 5x+13=3x-93 | | X=2-2 | | $45.00-30%= | | -3(m-7)=2m-4 | | 7x+2+2+3+8=180 | | -3x=x-20 | | 3x+5y=328 | | (-9)=b+(-13) | | 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) |

Equations solver categories